2014
DOI: 10.3109/08941939.2014.982313
|View full text |Cite
|
Sign up to set email alerts
|

End-to-End Invaginated Pancreaticojejunostomy with Three Overlapping U-Sutures––A Safe and Simple Method of Pancreaticoenteric Anastomosis

Abstract: The technique of using three overlapping U-sutures in an end-to-end invaginated pancreaticojejunostomy represents a simple management of pancreaticoenteric anastomosis with reliability and applicability, and provides an alternative choice for pancreaticojejunostomy to senior pancreatic surgeons as well as those without experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…[ 83 ] Several recent studies and meta-analyses have reported POPF results from various variations of surgical anastomotic techniques. [ 43 , 47 , 48 , 50 , 65 , 84 , 85 ]. Six meta-analyses [ 43 , 45–48 , 50 ] have investigated the effect of the two most commonly performed anastomotic techniques for creating continuity between the pancreas remnant and the gastrointestinal tract – pancreaticogastrostomy and pancreaticojejunostomy – and their effect on fistula rates, and found significantly different rates of POPF in all six meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…[ 83 ] Several recent studies and meta-analyses have reported POPF results from various variations of surgical anastomotic techniques. [ 43 , 47 , 48 , 50 , 65 , 84 , 85 ]. Six meta-analyses [ 43 , 45–48 , 50 ] have investigated the effect of the two most commonly performed anastomotic techniques for creating continuity between the pancreas remnant and the gastrointestinal tract – pancreaticogastrostomy and pancreaticojejunostomy – and their effect on fistula rates, and found significantly different rates of POPF in all six meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, surgeons have always directed their efforts at reducing the rate of pancreatic fistula through the introduction of new and effective methods of construction of the pancreatic anastomosis [14][15][16][17]. Various techniques have been described for joining the pancreatic stump either with the jejunum or with the stomach, with or without internal or external drainage of the pancreatic duct [18].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Kim et al [20] then modified Peng's technique, and after placing the stump 3 cm deep into the intestine, they used only two transpancreatic U-sutures securing the upper and lower border of the jejunum. Li et al [21] further published a new technique of pancreaticojejunal end-to-end anastomosis with two to four single interrupted U-sutures (Chen's U-suture), performed with double-armed sutures (Fig. 2).…”
Section: Modifications Of the Standard Invagination Techniquementioning
confidence: 99%